Effectiveness of iNTS vaccination in sub-Saharan Africa - Daniele Cassese; Nicola Dimitri; Gianluca Breghi; Tiziana Spadafina (Scientific Reports)
Abstract Invasive non-Typhoidal Salmonella (iNTS) is one of the leading causes of blood stream infections in Sub-Saharan Africa, especially among children. iNTS can be difficult to diagnose, particularly in areas where malaria is endemic, and difficult to treat, partly because of the emergence of antibiotic resistance. We developed a mathematical model to evaluate the impact of a vaccine for iNTS in 49 countries of sub-Saharan Africa. Without vaccination we estimate 9.2 million new iNTS cases among children below 5 years old in these 49 countries from 2022 to 2038, 6.2 million of which between 2028 and 2038. The introduction of a $$85%$$ ( $$95%$$ ) efficacy vaccine in 2028 would prevent 2.6 (2.9) million of these new infections. We provide the country-specific impact of a iNTS vaccine considering the different age structures and vaccine coverage levels.